Aerosol disinfection of weapons, internal volumes of military equipment and facilities - A. V. Kryuchkov; M. B. Smirnov; V. D. Krasakov (Вестник войск РХБ защиты)
The disinfection of weapons, internal volumes of military equipment and facilities is an important element in protecting the population and military personnel from biological agents. In order to increase the likelihood of contact of the disinfectant with the object of disinfection, to increase the activity of the disinfectant per unit of its mass, to reduce its consumption and the processing time, the liquid disinfectant preparations should be transferred effectively by the generator to a spray aerosol with a particle size of 1–30 µm. For the creation of such an aerosol, we have elaborated a special device – a tank with a lid with four diffusors, fixed on it and connected by air pipes made of rubber reinforced hose. The compressed air is supplied to the diffusors through a nozzle, fixed on the lid. An intake tube supplies disinfectant to the sprayers. This tube allows the solution to be dispensed for dispersion due to the ejection that occurs when compressed air is supplied. There is a neck, covered with micromesh, in the upper part of the lid, through which the filling process is carried out. The mesh also prevents solids from entering the tank, because the nozzles may get clogged, and that may lead to the disruption of the disinfectant dispersion process. There is a handle on the neck for the convenience of carrying the whole installation. Three short bearers are welded to the bottom of the tank, allowing the device to be installed on any horizontal surface. The dimensions of the device are: diameter – 270 mm, height – 195 mm. The volume of the tank for disinfectant is 5 dm3. The article also deals with the main techniques of using technical means for aerosol disinfection of premises and with the factors, affecting the quality of disinfection. The paper underlines the need for a systematic approach to the choice of technical means, disinfectants and modes of disinfection by the method of aerosol disinfection.